PERTUMBUHAN BIBIT KELAPA SAWIT PRE NURSERY DENGAN PEMUPUKAN SERUM DARAH KAMBING DAN PUPUK CAMPURAN (NPK DAN UREA) DI TANAH LATOSOL - Mei Diyanto; Enny Rahayu; Retni Mardu Hartati (Program Studi Agroteknologi INSTIPER, 2017)
The objective of this research was to find out whether goat blood serum and fertilizer combination can improve the growth of oil palm seedlings in pre nursery. This research was conducted at Plantation for education and observation, Stiper Agricultural Institute which located in Yogyakarta. This research was conducted from January until April 2017, using two factorial experiments arranged in completely random design (CRD). The first factor was the concentration of goat blood serum, concentration of 10%, 20%, and 30%. The second factor was combination of fertilizer, combination of NPK and Urea 1 gram / liter, 2 gram / liter, and 3 gram / liter. The result of analysis of variance showed that the concentration of goat blood serum had only significant effect on root dry weight and root volume, and the best concentration was 20%. However, no significant affected on the other parameters. The interaction of NPK and Urea fertilizers has no significant effect on the growth of oil palm seedlings